2008
DOI: 10.1016/j.virol.2008.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic machinery activated by dengue virus enhances virus replication

Abstract: Autophagy is a cellular response against stresses which include the infection of viruses and bacteria. We unravel that Dengue virus-2 (DV2) can trigger autophagic process in various infected cell lines demonstrated by GFP-LC3 dot formation and increased LC3-II formation. Autophagosome formation was also observed under the transmission electron microscope. DV2-induced autophagy further enhances the titers of extracellular and intracellular viruses indicating that autophagy can promote viral replication in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
330
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(350 citation statements)
references
References 27 publications
19
330
1
Order By: Relevance
“…Although flavivirus induces apoptosis of neurons and macrophages, infected hepatocytes and epithelial cells do not die. We find that flavivirus up-regulates autophagy in MDCK 3 renal epithelial cells and other cell types and subsequently protects them. We further identify nonstructural protein NS4A of both Dengue-2 and Modoc viruses as the sole viral mediator of autophagy up-regulation and protection against death.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Although flavivirus induces apoptosis of neurons and macrophages, infected hepatocytes and epithelial cells do not die. We find that flavivirus up-regulates autophagy in MDCK 3 renal epithelial cells and other cell types and subsequently protects them. We further identify nonstructural protein NS4A of both Dengue-2 and Modoc viruses as the sole viral mediator of autophagy up-regulation and protection against death.…”
mentioning
confidence: 75%
“…Flaviviruses often persist in liver and kidney following the acute phase of infection, suggesting that infected cells evade destruction by the host immune response, likely by flavivirusinduced up-regulation of autophagy in these cells. In vitro infection of hepatocytes and fibroblasts leads to up-regulation in autophagy and protection against death (3,4). More relevant, Dengue-2 viruses replicate within the hepatocyte autophagosomes (5), and inhibition of autophagy attenuates virus replication (3).…”
mentioning
confidence: 99%
“…A distinct example is dengue virus (DENV), a virus in the Flavivirus genus and therefore more closely related to HCV. DENV infection has been shown to induce autophagy which promotes viral replication (Lee et al, 2008). Furthermore, it was observed that the DENV NS1 protein and dsRNA (as markers of replication complexes) colocalized with LC3, the ribosomal protein L28 and the mannose 6-phosphate receptor, suggesting that the DENV replication/translation machinery is present on amphisomes, which result from the fusion of autophagosomes and endosomes (Panyasrivanit et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced activation of autophagy by rapidly replicating bacteria such as wBm during larval development and in adult worm populations and induced by wMelPop in Drosophila also may influence the successful infection and transmission of viruses. For example, the requirement of arboviruses (Dengue and Chikungunya) for an intact host autophagy system and their use of autophagosomes for successful replication and transmission (34,35) may be blocked by Wolbachia-mediated manipulation of autophagosomal maturation, a hypothesis we are testing currently.…”
Section: Discussionmentioning
confidence: 99%